„PAMYAT’ DAMA ZABYVCHAYA“ – THE GREAT PATRIOTIC WAR: MYTHOLOGIZED OR DOOMED TO OBLIVION - Pazio-Wlazłowska, Dorota (Porównania, 2012)
By discussing the history of the center for the Great Patriotic War veterans opened on the Island of Valaam (the Republic of Karelia, Russia) in the early 1950s, the article searches for the roots and reasons for the “social oblivion“ that affected the war wounded veterans, many of them amputees. The author tries to point to the mechanisms that account for the discrepancies between the official myth of the brave and simple soldier, respected and admired by the younger generations, and the grim fate of the crippled war veterans doomed to oblivion. She emphasizes that when it comes to the Great Patriotic War, social oblivion has often “competed” with social remembrance. She also shows what kind of filters have been applied to the Russian collective memory, and how the elements not fitting the official gala image of war veterans have been excluded as they could potentially undermine the shared group identity.